Primary care trust commissioning of varicose vein intervention – New guidance needed?. (September 2014) - Griffin, Kathryn Jane; Cousins, Simon; Bailey, Marc Aaron; Berridge, David; Scott, David Julian Ashbridge
Objectives: In light of evidence of national variability in service commissioning of varicose vein intervention, our aim was to evaluate the current state of primary care trust commissioning for all forms of varicose vein intervention in England. We also sought to clarify the extent to which access to endovenous and surgical varicose vein services is being restricted. Methods: Under the Freedom of Information Act (2001), a structured email survey was sent to 108 primary care trusts in England. Trusts were asked how many elective endovenous laser therapy and open procedures were commissioned from 2008 to 2011 and they were asked to submit their commissioning policy for analysis. The 'qualifying criteria' expressed in each policy were analysed by theme and geographical region. Results: Of 108 surveys, 95 (88%) were completed and returned. Of these, 91 (96%) stated that varicose vein interventions were actively commissioned. Eighty-eight (97%) of primary care trusts that commissioned varicose vein interventions stated that access was restricted. Qualifying criteria varied considerably between regions. Conclusions: Access to varicose vein intervention appears to be restricted, with national variation in commissioning across England. This might have an impact on patient care and surgical training. We propose that a national decision be made about which varicose vein patients should be offered funding for treatment on the National Health Service.